Assessing restoration and degradation of natural and artificial vegetation in the arid zone of Northwest China - Zhang, Jinxia; Li, Zhi; Duan, Weili; Zhao, Hongfang; Hao, Haichao; Xiang, Yanyun; Zhang, Qifei (Frontiers in Ecology and Evolution, 2023)
Assessing vegetation restoration and degradation trends is important for regional ecological conservation and sustainable development, yet few studies have examined the characteristics of these trends in natural and artificial vegetation in arid zones. In this study, we develop an assessment framework based on two common ecological indicators, Net Primary Productivity (NPP) and Water Use Efficiency (WUE). We discuss the restoration and degradation trends of natural and artificial vegetation in China’s Northwest Arid Region (NAR) and analyse the similarities and differences between the changes in the two. Our results reveal the following: 1) Both natural vegetation (Nav) NPP and artificial vegetation (Arv) NPP in the NAR are dominated by significant growth, with precipitation being the most influential factor. Arv NPP changes are greater than Nav NPP. 2) WUE and NPP have similar spatial distribution characteristics, with precipitation and temperature dominating WUE changes in the Qilian Mountains and s southern Xinjiang, respectively. In the near future, Nav WUE is expected to be dominated by improvement to degradation, while Arv WUE will continue to improve under human intervention. These two indices respond differently to the environmental factors that cause their changes. 3) Nav and Arv exhibit similar restoration and degradation trends, mainly dominated by early recovery with Nav displaying a slightly more prominent restoration trend than Arv. The NPP-WUE assessment framework will help to rapidly assess vegetation degradation and restoration at large scales, providing new perspectives for research in this field.